Managing Future Meat Consumption Fulfilment in Indonesia - Wendy Imam Fauzie; Manahan Parlindungan Siallagan (Journal of Business and Management Review, 2023)
Peer level of animal proteins for Indonesians reach low level of consumption-per-capita (CPC), this low protein consumption is strongly associated with malnutrition. Supply and demand take a part in several studies, supply-side approval meets consumption needs. Herd size, livestock shed, and production efficiency impacting the land mass area and environment. Beef meat consumption is inherently dependent on several interlinked and dynamic system modelling. One such methodology like modelling interactive systems in multivariate impact will yield the greatest overall increase in beef supply consequently. Using systems modelling tools, the researcher tries to simulate how beef consumption patterns are a dependent factor of several interrelationships with systems thinking. The alternative cluster structure is divided into 2 parts, tax policy and budget policy, which are the source of the budget scheme. Two of the six alternative policies were selected as the best choices with acceleration of output achievement. The higher tax rate is a consequence of a depressed level of demand, which has implications for national per capita consumption.